The buckling behaviour of steel plate as a column / Rosli Mohd Amin - Mohd Amin, Rosli (1997)
The main scope of this project is to study the buckling behaviour of steel plate as a column. We consider the overall buckling for the tested specimens. We study the Modulus of Elasticity (E) of the material related to the lateral displacement (8) subjected to axial compression load. That is to check the local modulus of elasticity at point where the displacement are being measured, calculated and analysed by computer analysis. Finite Element Method is known exclusively to solve structural engineering problems. This project uses the package programmes "ANALYSIS SYSTEM" (ANSYS) to compare the lateral displacement of a steel plate column due to an axial compression load during buckling. The comparison from the theoritical and the experimental results will be carried out. The ANSYS programming using eigenvalue (or linear) buckling analysis, which is based on stress-stiffening theory by using element "SHELL 43" will be used to iterate the values of the modulus of elasticity, until the experimental lateral displacement is achieved. The initial of modulus of elasticity used in the ANSYS was taken from the tensile test result. The stresses induced during the buckling condition will be determined at maximum lateral displacement of the steel plate column.